2D Colloidal Nanoplatelets based Optoelectronics. Issue 30 (28th June 2016) - Robin, Adrien; Lhuillier, Emmanuel; Dubertret, Benoit
ABSTRACT: Two-Dimensional materials open up great prospects in photodetector applications owing to their sharp optical properties and the ability to combine them in layered heterostructures. Among this new class of materials, colloidal nanoplatelets (NPL) made of cadmium chalcogenides readily combine the thickness control at the atomic level together with the large scale production and ease of processing of colloidal materials. As a strategy to overcome the limited mobility inherent to nanocrystal based devices, the photocarrier lifetime is increased by building an electrolyte-gated phototransistor to passivate the electron traps. NPL can also be coupled with a graphene transport layer collecting the photogenerated charges, thus bypassing the transport bottleneck. We show that the charge transfer is driven by the large exciton binding energy of the NPL, which can be engineered by heterostructured NPL. This allows us to control the magnitude and the direction of the charge transfer to graphene. Eventually, we use nanotrench electrodes to decrease the transit time of the carriers, suppress the influence of film defects and provide an electric field large enough to overcome the large exciton binding energy of NPL.